Cover Picture: A High‐Valent Heterobimetallic [CuIII(μ‐O)2NiIII]2+ Core with Nucleophilic Oxo Groups (Angew. Chem. Int. Ed. 21/2013). Issue 21 (29th April 2013) - Kundu, Subrata; Pfaff, Florian Felix; Miceli, Enrico; Zaharieva, Ivelina; Herwig, Christian; Yao, Shenglai; Farquhar, Erik R.; Kuhlmann, Uwe; Bill, Eckhard; Hildebrandt, Peter; Dau, Holger; Driess, Matthias; et al.
<x xml:space="preserve">Abstract</x> Unlike typical homodinuclear high‐valent [M2(μ‐O)2]n+ cores, a rare heterobimetallic high‐valent CuNi bis(μ‐oxo) complex behaves as a nucleophile. In their Communication on page 5622 ff., K. Ray, M. Driess, C. Limberg et al. show that this complex can initiate deformylation of aldehydes, indicating that mixed‐metal bis(μ‐oxo) cores are viable intermediates in the deformylation of fatty aldehydes by cyanobacterial aldehyde decarbonylase, for which a similar cofactor has been suggested, but not isolated.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>